An Alignment Method of Human-Robot Collaboration Based on the Six-Dimensional Force/Torque Dynamic Measurement for Large-Scale Components - Ke Wen; Fuzhou Du; Jiabo Zhang; JiZhi Yang (Journal of Robotics)
A Stewart parallel robot (SPR) is a promising choice for alignment or assembly of components that are large or heavy. This paper presents a method for human-robot collaboration, for positioning and orientation of large components. Use of interactive force measurements is important for human-robot collaboration. It is based on six-dimensional force/torque (F/T) measurements. First, the six-dimensional F/T data are calculated based on the six-actuator SPR geometry and screw theory. Second, the effects of gravity forces (dynamic gravity compensation) are considered, and a method to offset their effects is explained. Third, force estimation experiments were performed using an S-type force sensor and known applied test forces. Finally, the F/T-driven feedback was tested for the alignment of a large-scale component. The experimental results show that the calculated six-dimensional F/T can accurately track the force applied to a large and/or heavy component by a human worker. It can also accurately predict the F/T required to compensate for inertial forces and components’ weight. Thus, the alignment method of human-robot collaboration based on the six-dimensional force/torque dynamic measurements for large-scale components is correct and effective.